Comparison among Different Constitutive Equations on Investigating Tensile Plastic Behavior and Microstructure in Austempered Ductile Iron - Angella, Giuliano; Zanardi, Franco (Journal of Casting & Materials Engineering, 2018)
The capabilities of different constitutive equations of approximating the tensile flow curves and correlating plastic behavior with the microstructure were investigated in austempered ductile iron ADI 1050. In a previous paper, the microstructure evolution of ADI 1050 during austempering was investigated through quenching the ADI 1050 after 14 increasing austempering times to room temperature. The 14 samples were tensile tested and two classes of constitutive equations were examined in the present paper. The Hollomon-type constitutive equations approximated all of the tensile flow curves of ADI 1050 very well but failed in correlating the plastic behavior with microstructure evolution. Voce-type constitutive equations approximated the tensile flow curves only at high stresses very well but could correlate the plastic behavior with the microstructure evolution of ADI 1050 during austempering excellently. The reason of this success was rationalized in terms of the physical basis of Voce-type equations, while Hollomon-type equations are empirical.